Control of plasma membrane lipid homeostasis by the extended synaptotagmins - Saheki, Yasunori (2016)
Acute metabolic changes in plasma membrane (PM) lipids, such as those mediating signalling reactions, are rapidly compensated by homeostatic responses whose molecular basis is poorly understood. Here we show that the extended synaptotagmins (E-Syts), endoplasmic reticulum (ER) proteins that function as PtdIns(4,5)P2- and Ca2+-regulated tethers to the PM, participate in these responses. E-Syts transfer glycerolipids between bilayers in vitro, and this transfer requires Ca2+ and their lipid-harbouring SMP domain. Genome-edited cells lacking E-Syts do not exhibit abnormalities in the major glycerolipids at rest, but exhibit enhanced and sustained accumulation of PM diacylglycerol following PtdIns(4,5)P2 hydrolysis by PLC activation, which can be rescued by expression of E-Syt1, but not by mutant E-Syt1 lacking the SMP domain. The formation of E-Syt-dependent ER–PM tethers in response to stimuli that cleave PtdIns(4,5)P2 and elevate Ca2+ may help reverse accumulation of diacylglycerol in the PM by transferring it to the ER for metabolic recycling.